The Role of Video Games in Shaping National Identity Awareness in the Kingdom of Bahrain - Alsridi, Hatem; Juma, Mariam; Jallaf, Yousif; Alabed, Abdullah (Journal of Cultural Analysis and Social Change, 2025)
The study aims to examine the impact of video games on enhancing awareness of national identity in the Kingdom of Bahrain, focusing on the potential of this digital medium as an educational and cultural tool that instils values of belonging and pride in national heritage. The research addresses a key question regarding the role of video games in solidifying and promoting Bahraini national identity among users. The study adopted a quantitative approach, using a questionnaire administered to a sample of 406 individuals who engaged with video games featuring elements of Bahraini national identity. The study found that video games positively enhance a sense of belonging and revealed that incorporating cultural symbols and elements into games increases awareness of national identity and encourages exploration of its meanings. It indicated that presenting this type of game in an interactive context encourages sustained engagement, as participants interacted in various ways through sharing, researching, conceptual improvement, and learning. The study concluded that integrating elements of national identity into video games enhances national awareness but requires further development and collaboration with additional entities to ensure sustainable impact. However, the influence in some areas remains limited due to the field's novelty in the Kingdom of Bahrain and the scarcity of games.